2020
DOI: 10.1016/j.isci.2020.101187
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6B Greatly Increases Risk of Depression by Activating Hypothalamic-Pituitary -Adrenal Axis during Latent Phase of Infection

Abstract: We identified SITH-1, a new protein specific to HHV-6B latent infection Mice expressing SITH-1 at HHV-6B latent infection site had depressive symptoms Depressive symptoms due to SITH-1 were associated with a hyper-activated HPA axis SITH-1-specific antibody detection significantly greater in depressive patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 40 publications
0
46
3
1
Order By: Relevance
“…A recent study suggested that salivary HHV-6 DNA is associated with the decreased hippocampal neurogenesis and the development of depression through the olfactory bulb apoptosis. 7 In this study, however, no patient developed depression despite the high incidence of high-level salivary HHV-6 DNA. Our data did not support the hypothesis that salivary HHV-6 DNA has a role in the development of depression in the setting of allogeneic HSCT.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A recent study suggested that salivary HHV-6 DNA is associated with the decreased hippocampal neurogenesis and the development of depression through the olfactory bulb apoptosis. 7 In this study, however, no patient developed depression despite the high incidence of high-level salivary HHV-6 DNA. Our data did not support the hypothesis that salivary HHV-6 DNA has a role in the development of depression in the setting of allogeneic HSCT.…”
Section: Discussioncontrasting
confidence: 47%
“…6 A recent study suggested that salivary HHV-6 DNA is associated with the decreased hippocampal neurogenesis and the development of depression through the olfactory bulb apoptosis. 7 These findings raise the possibility that salivary HHV-6 has pathogenic roles in the development of oral mucosal chronic GVHD, depression, and neurological diseases in allogeneic HSCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In their seminal stage model, Lazarus and Folkman ( 1984 ) suggest that individuals first appraise a given stressor as harmful, threatening, or challenging, and then evaluate whether sufficient resources are available to cope with the situation, which in turn determines the level of distress they are experiencing (Cohen et al 2016 ; Krohne 2001 ). In this sequential view of the stress process, maladaptive appraisals and coping mechanisms are crucial factors in explaining the link between psychopathology and stress (Kobayashi et al 2020 ). Therefore, understanding mechanisms and behaviors that affect appraisal and coping is pivotal in the prevention of mental health issues and the promotion of global mental health (Jenkins 2019 ; Kirmayer and Pedersen 2014 ).…”
mentioning
confidence: 99%
“…Since the discovery of human beta-herpesviruses and their ability to persist lifelong in their hosts, augmented interest in the possible role of the virus in development of neurodegenerative and mood diseases has been shown [ 6 , 15 , 16 , 47 ]. Our study used autopsy materials of frontal and temporal cortical and subcortical areas of 48 individuals with and without (controls) diagnosis of unspecified encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…During persistent viral infection, clinical manifestations may frequently not even appear. However, the putative long term influence is associated with the central nervous system (CNS) diseases such as encephalitis, Alzheimer’s disease, multiple sclerosis, and has a role in tumorigenesis and mood disorders [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%